Enhancing Local Government Capacity for Sustainable Tourism Sector Development in Batam City: An Assessment of Human Resources, Management, and Network Cooperation - Melanda Pramita Indah; Timbul Dompak; Lubna Salsabila (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2023)
The purpose of this study is to evaluate the capacity building efforts made by the city government of Batam in the pursuit of nurturing a tourism industry that is sustainable. This study used a descriptive qualitative methodology, conducting semi-structured interviews with four key informants from the Batam City Culture and Tourism Office in order to gather information for the study. According to the findings, the municipal government, and in particular the Department of Culture and Tourism, has experienced major difficulties in meeting the quality and quantity of human resources, as well as in maintaining internal management and establishing collaborative networks. This is especially true in light of the findings. As a direct result of this, the tourism industry in Batam City has been experiencing a period of stagnation as well as a decrease in interest from both domestic and international visitors. At the present day, the primary function of Batam is to act as a transit hub for tourists going to neighboring countries such as Malaysia and Singapore. The administration of potential tourist locations has been made more difficult due to a lack of human resources, which has resulted in a decline in employee performance and hampered operations related to internal management. Because of this, the formation of networks and cooperation with other stakeholders, both locally and regionally, which are important for the development of tourism in Batam City are hampered.